2010
DOI: 10.1002/bies.200900148
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic functions of the PDZ‐LIM protein family: new insights into organ development

Abstract: Recent work on the PDZ-LIM protein family has revealed that it has important activities at the cellular level, mediating signals between the nucleus and the cytoskeleton, with significant impact on organ development. We review and integrate current knowledge about the PDZ-LIM protein family and propose a new functional role, sequestering nuclear factors in the cytoplasm. Characterized by their PDZ and LIM domains, the PDZ-LIM family is comprised of evolutionarily conserved proteins found throughout the animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 99 publications
2
85
0
Order By: Relevance
“…In addition to regulating collagen fibrillogenesis, LUM has been reported to inhibit cell migration in melanoma cells and human mesenchymal stem cells via integrin ␤1 (64,65). PDLIM1/Elfin binds to filamentous actin-associated proteins and regulates organ development (66,67). In agreement with its heightened activity on cell spreading, PRB-K464Q mediated greater induction of LUM and PDLIM1 by R5020 as compared with WT PRB (Fig.…”
Section: Lys-464 Mutations Alter Markedly Pr-mediated Progestin Respomentioning
confidence: 68%
“…In addition to regulating collagen fibrillogenesis, LUM has been reported to inhibit cell migration in melanoma cells and human mesenchymal stem cells via integrin ␤1 (64,65). PDLIM1/Elfin binds to filamentous actin-associated proteins and regulates organ development (66,67). In agreement with its heightened activity on cell spreading, PRB-K464Q mediated greater induction of LUM and PDLIM1 by R5020 as compared with WT PRB (Fig.…”
Section: Lys-464 Mutations Alter Markedly Pr-mediated Progestin Respomentioning
confidence: 68%
“…PDLIM5 acts as an adaptor protein to Relative units sequester transcription factors in the cytoplasm or interacts with kinases to exert its effects (57,(59)(60)(61)(62). Consistent with decreased miR-17z92 in APAH PASMC, PDLIM5 is up-regulated in APAH but not in IPAH PASMC ( Figure 6; Figure E11).…”
Section: Original Articlementioning
confidence: 70%
“…In an attempt to identify the mechanism underlying the positive regulation of TGF-b 3 /Smad3 by miR17z92 in PASMC, we found that miR-17/ 20a directly suppressed PDLIM5 (Figure 4; Figures E4 and E5), a member of the PDZ-LIM protein family, that acts as a signal modulator to influence organ development and different disease states (57,58). PDLIM5 acts as an adaptor protein to Relative units sequester transcription factors in the cytoplasm or interacts with kinases to exert its effects (57,(59)(60)(61)(62).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Enigma enhances bone morphogenetic responsiveness by interacting with Smad ubiquitin-regulatory factor 1 (22). Recently, pdlim7 in zebrafish has been shown to be involved in heart and skeletal muscle development (23). However, the exact cellular functions of Enigma remain enigmatic.…”
Section: Introductionmentioning
confidence: 99%